Analysis of Structure and Functional Group of Filament Product-Based PLA/Nanographite Nanocomposite - Suryanto, Heru; Aminnudin, Aminnudin; Bintara, Redyarsa Dharma; Putra, Abyan Farras; Nashrullah, Fikri Munif; Binoj, Joseph Selvi; Panicker, Nithin (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
In many polymer compounds, Polylactic Acid (PLA) is a polyalcohol material that has the most potential material which is potent for biological degradation. They have been applied as filaments in additive manufacturing. The PLA properties can be modified by adding nanomaterials such as graphite nanoplatelets. This study aims to obtain the characteristics of PLA-based filament nanocomposite with nanographite reinforcement. Methods include exploration research to obtain nanocomposite filament with PLA and 1% of nanographite. The mixing process of nanographite in PLA solution with chloroform solvent and then the extrusion process of nanocomposite using a single extruder. The product comparison before and after the extrusion process was analyzed using X-ray diffraction and Fourier Transform infrared. Diffractogram results indicate that the original PLA structure is amorphous, and after mixing using nanographite, peaks of nanographite appeared clearly. After the extrusion process, some peaks at 16.7° and 19.1° disappeared, but only a peak 26.6° appeared in the diffractogram. Extrusion makes the structure change. Functional group analysis confirms that some reactions occurred so that many peaks were removed, and several new peaks were observed. It indicates that the extrusion process of PLA/nanographite results in different structures and functional groups that indicate a change in its properties.